No need to discriminate? Reproductive diploid males in a parasitoid with complementary sex determination. - Jan Elias (Public Library of Science (PLoS), 2009)
Diploid males in hymenopterans are generally either inviable or sterile, thus imposing a severe genetic load on populations. In species with the widespread single locus complementary sex determination (sl-CSD), sex depends on the genotype at one single locus with multiple alleles. Haploid (hemizygous) individuals are always males. Diploid individuals develop into females when heterozygous and into males when homozygous at the sex determining locus. Our comparison of the mating and reproductive success of haploid and diploid males revealed that diploid males of the braconid parasitoid Cotesia glomerata sire viable and fertile diploid daughters. Females mated to diploid males, however, produced fewer daughters than females mated to haploid males. Nevertheless, females did not discriminate against diploid males as mating partners. Diploid males initiated courtship display sooner than haploid males and were larger in body size. Although in most species so far examined diploid males were recognized as genetic dead ends, we present a second example of a species with sl-CSD and commonly occurring functionally reproductive diploid males. Our study suggests that functionally reproductive diploid males might not be as rare as hitherto assumed. We argue that the frequent occurrence of inbreeding in combination with imperfect behavioural adaptations towards its avoidance promote the evolution of diploid male fertility.